Magmatic signature in acid rain at Masaya volcano, Nicaragua: inferences on element volatility during lava lake degassing - Liotta, Marcello; Martínez Cruz, María; Ferrufino, Arnoldo; Rüdiger, Julian; Gutmann, Alexandra; Rojas Cerda, Kathia V.; Bobrowski, Nicole; de Moor, J. Maarten (Chemical geology, 2021)
Major, minor and trace element concentrations of single rainfall events were investigated at Masaya volcano (Nicaragua) in order to determine the relative contributions of volcanogenic elements. Most of the samples were collected in the summit area of the volcano around the Santiago crater, and two samples, representative of the local background, were collected at a 4.3 km upwind site. Samples from the summit are very acidic with pH down to 2.14 and contain large amounts of volcanogenic elements that can be clearly distinguished from the local background. These elements are released into the atmosphere from the continuously degassing lava lake of the Santiago crater, Masaya volcano. The emissions result in a volcanic plume that includes solid particles, acidic droplets, and gaseous species. The plume-rain interaction imprints the chemical signature of the volcanic emissions in falling raindrops. The most acidic gases (e.g. HCl and HI) readily dissolve in water, and so their ratio in rain samples reflects that of the volcanic plume. The transport of HF is mediated by the large amount of silicate particles generated at the lava-air interface. SO2 is only partially converted into H2SO4 that dissolves in water. The refractory elements dissolved in rain samples derive from the dissolution of silicate particles, and most of them (Al, Mg, Ca, Fe, Be, Ti, Mn, and Sr) are present at exactly the same molar ratios as in the rocks as well as rare earth elements (REEs). By contrast, Li, Na, K, Cr, Ni, Cu, Zn, Rb, Cd, Sb, Te, Cs, Tl, Pb, and Bi are enriched relative to the whole-rock composition, suggesting that they are volatilized during magma degassing. After correcting for the dissolution of silicate particles, we can define the relative volatility of these elements. The comparison with other volcanoes on the Pb emissions highlights the effect of oxygen fugacity in determining its volatility.